(untitled) (Research, Society and Development, 2021)
Tucumã pulp (Astrocaryum aculeatum Meyer) has high nutritional value and is widely accepted in the northern region of Brazil. However, there are few studies reporting the intrinsic properties and the rate of contamination of these products. The objective of this work was to evaluate the physical-chemical characteristics and the microbiological quality of tucuma pulp commercialized in fairs in the city of Manaus-AM. In this study two samples were acquired from each zone of the city of Manaus, Center-West zone (ZCO), Center-South zone (ZCS), East zone (ZL), North zone (ZN), West zone (ZO), South zone (ZS). The samples were evaluated for their physical-chemical characteristics (pH, humidity, total soluble solids expressed in ºBrix, titratable acidity expressed in citric acid and ratio). In determining the microbiological quality the presence of Escherichia coli, Salmonella sp. and molds and yeasts were evaluated. The ZCS2 pulp presented a significant quantity of pH (5.14). The average moisture content was 57.28% and the acidity expressed as citric acid ranged from 0.03% to 0.13%. ZL2 showed significant values for total solids (5.13 °Brix) and ratio (128.33). ZCO2, ZS1 and ZL1 pulps showed E.coli counts higher than the Brazilian legislation (10 MPN/g). ZL1 sample showed significant counts of mold and yeast (2.1 x 104 CFU/g). The results obtained in the present study indicate the need for improvements in the control of the sanitary quality of tucumã pulp commercialized in the fairs of the city of Manaus-AM.